A Prospective Observational Analysis of Endometrial Cancer Risk Associated with Thyroid Hormone Dysregulation: Research Article (Journal of Pharma Insights and Research, 2024)
This prospective observational study investigated the relationship between thyroid dysfunction and the risk of developing endometrial cancer in a cohort of 100 patients diagnosed with endometrial cancer. Patient data including demographics, medical history, thyroid function tests (T3, T4, TSH levels), and comorbidities (diabetes mellitus and hypertension) were collected. Thyroid dysfunction was defined as T3, T4, or TSH levels outside the reference ranges (T3: 0.8-2.0 ng/mL, T4: 5.1-14.1 ug/dL, TSH: 0.27-4.2 uIU/mL). Logistic regression analyses were performed to evaluate the association between thyroid dysfunction and endometrial cancer risk, adjusting for potential confounders. The study population had a mean age of 55.9 years (range: 35-82 years). Out of 100 patients, 28 (28%) exhibited hypothyroidism (low T3 or T4, or high TSH), and 12 (12%) exhibited hyperthyroidism (high T3 or T4, or low TSH). Univariate logistic regression analysis revealed a significant association between hypothyroidism and endometrial cancer risk (OR = 2.14, 95% CI: 1.22-3.76, p = 0.008). After adjusting for age, diabetes, and hypertension, the multivariate logistic regression analysis showed that hypothyroidism remained an independent risk factor for endometrial cancer (OR = 1.92, 95% CI: 1.07-3.45, p = 0.029). However, the association between hyperthyroidism and endometrial cancer risk was not statistically significant (OR = 1.34, 95% CI: 0.64-2.82, p = 0.439). This study provides evidence for a significant association between hypothyroidism and increased risk of endometrial cancer, independent of age, diabetes, and hypertension. Further research is needed to understand the underlying mechanisms and explore the potential implications for screening and management strategies